Pengaruh Kompetensi Terhadap Kinerja Pegawai pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Kabupaten Maluku Tengah - Tuarita, Jauhari; Rahawarin, Mohamad Arsad; Bahasoan, Aminah (Jurnal Ilmiah Global Education, 2025)
This study aims to analyze the influence of technical, managerial, social, strategic, and ethical competencies on employee performance at the Personnel and Human Resources Development Agency (BKPSDM) of Central Maluku Regency. The research employed a quantitative survey method, collecting data through questionnaires from 46 employees. Data analysis was conducted using multiple linear regression to examine both partial and simultaneous effects of the variables. The results indicate that technical and managerial competencies have a positive and significant impact on employee performance, while social, strategic, and ethical competencies do not show significant individual effects. Simultaneously, all five competencies positively and significantly affect employee performance, with a coefficient of determination (R²) of 0.919, indicating that 91.9% of performance variations can be explained by the combination of these competencies. These findings highlight the importance of developing multiple dimensions of competencies in an integrated manner to enhance employee performance in public institutions. The study provides implications for human resource development policies, including technical training, managerial capacity building, and fostering social and ethical competencies.